1998
DOI: 10.1021/bi9730442
|View full text |Cite
|
Sign up to set email alerts
|

Specific Cross-Links between Fragments of Proteolyzed Na,K-ATPase Induced by o-Phthalaldehyde

Abstract: We have used o-phthalaldehyde (OPA) to cross-link adjacent fragments of "19 kDa membranes", a tryptic preparation of Na,K-ATPase lacking the ATP site but retaining cation occlusion sites. Treatment with OPA of "19 kDa membranes" or detergent-solubilized membranes containing occluded Rb ions [Or, E., Goldshleger, R., Tal, D. M., and Karlish, S. J. D. (1996) Biochemistry 35, 6853-6864] yielded cross-linked products of 25 and 31 kDa. Both species contained the 19 kDa fragment of the alpha subunit (transmembrane s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…This loop appears to be the focal region for ␥-␣-␤ interactions. Accordingly, at the extramembranous extracellular region, the ␤ subunit interacts with L7/8 of ␣1 as shown in several earlier studies (19,(33)(34)(35)(36), and ␥ can also be cross-linked to ␤ (19), and as already suggested (19), the site of ␥-␤ interaction is probably close to the site of ␣-␤ interaction.…”
Section: ␥B-transfectedsupporting
confidence: 65%
“…This loop appears to be the focal region for ␥-␣-␤ interactions. Accordingly, at the extramembranous extracellular region, the ␤ subunit interacts with L7/8 of ␣1 as shown in several earlier studies (19,(33)(34)(35)(36), and ␥ can also be cross-linked to ␤ (19), and as already suggested (19), the site of ␥-␤ interaction is probably close to the site of ␣-␤ interaction.…”
Section: ␥B-transfectedsupporting
confidence: 65%
“…OPA reacts with thiols and primary amines yielding highly fluorescent 1-alkylthio-2-alkylisoindoles. The compound has been successfully used to determine the interaction between the subunits of Na + , K + -ATPases (Khan et al, 1996;Or et al, 1998). In this study, we have treated solubilized PMs from potato wild-type plants with OPA.…”
Section: Confirmation Of St Sut1 Dimerization By Alternative Methodsmentioning
confidence: 99%
“…This specific arrangement is not compatible with membrane insertion mediated only by intramolecular interactions and has required, during evolution, the association of a helper protein that assists the correct packing of K ϩ -transporting P-type ATPases. Or et al (48) previously suggested that the M7-M8 loop interacts with M4-M6 containing the cation sites so that disruption of the ␣-␤ interaction alters the disposition of this loop and inactivates cation occlusion. Our results strengthen this hypothesis, that is we provide evidence that the C-terminal regions of Na ϩ ,K ϩ -ATPase and H ϩ ,K ϩ -ATPase are likely to be involved in K ϩ de-occlusion.…”
mentioning
confidence: 99%